The Rockford files. Season four [videorecording (DVD)] - Garner, James, 1928-2014
" ... James Garner stars as the ex-con-turned-private-investigator who stays under the radar and takes on the cases of the lost and dispossessed, chasing down seemingly long-dead clues on the sunbaked streets and seamy alleys of Los Angeles. ..."--Set container.